Enhanced recovery of oil from Jatropha curcas L. seeds: ENHANCED RECOVERY OF OIL FROM JATROPHA CURCAS L. SEEDS - R ANANDALAKSHMI; V SIVAKUMAR; T VAMADEVAN; N KRISHNA KUMAR (Journal of Oilseeds Research, 2015)
Jatropha curcas L. is a popular and potential tree borne oilseed exploited for biofuel, however, extraction of oil from whole seedsincurs oil loss due to adsorption of considerable amount of oil to the oil cake. To minimize the oil loss, seeds were decoated using a seed decoater which separates the whole seedsinto shell and kernel. Seeds with 15 per cent of the shell removed and with 40 per cent of the shell removed were compared with whole seeds for oil extraction. The oil present in the oil cake was estimated and analysed for its physico-chemical properties. The average oil recovery from the whole seed was about 23.16 per cent. Removal of 15 per cent shell increased the oil recovery to 24.6 per cent and further removal of 40 per cent shell resulted in 25.41 per cent oil recovery. The oil present in the oil cake was reduced from 10.08 to 8.93 and 7.61 per cent in the 15 per cent shell removed and 40 per cent shell removed seeds, respectively. However, the physico-chemical properties of oil from oilcake did not vary significantly. From a commercial point of view, this study helped to enhance oil recovery and displayed the significance of seed processing technique.